Meningkatkan Daya Saing UMKM Perikanan Melalui E-commerce - Alpiani, Alpiani; Amri, Andi; Tahang, Hamzah; Fakhriyyah, Sitti; Wahid, Abd (Jurnal Visi Pengabdian Kepada Masyarakat, 2025)
The development of digital technology has opened up opportunities for MSMEs to expand their product marketing through the use of e-commerce. However, many MSMEs in the fishery sector in Takalar Regency have not yet optimally utilized digital platforms. This condition encourages the need for efforts to increase digital literacy and the capacity of fishery MSMEs in online marketing. The Fisheries Agribusiness Study Program at Hasanuddin University (Unhas) conducted community service activities with the theme " E-commerce for MSMEs: Opening Global Market Opportunities through Digital Marketing". This activity aims to provide understanding to MSMEs so they can utilize e-commerce as a means of marketing and business development. The implementation method includes presentations, simulations, and question-and-answer sessions integrated with the practice of using e-commerce. The results of the activity indicate an increase in the understanding and skills of fishery MSMEs in utilizing e-commerce. The use of e-commerce is expected to help fishery MSMEs overcome marketing constraints, increase sales, improve the welfare of business actors, and support regional economic growth.